Lexicographic Treatment of Negation in Sepedi Paper Dictionaries - Prinsloo, D.J. (Lexikos, 2020)
Negation in Sepedi is a complex matter — a variety of negative morphemes are used across complicated verbal and copulative structures and these morphemes are not interchangeable. Dictionary users in a text production situation need to be guided to the correct compilation of negative constructions. In most cases negative morphemes are not lemmatised in Sepedi paper dictionaries or if they are, the lexicographic treatment is inadequate. This paper provides an inventory of negation from which an abstraction of the negative morphemes is given. This is followed by a critical evaluation of Sepedi dictionaries and suggested model entries for lexicographic treatment of negative morphemes.